2013
DOI: 10.4271/2013-01-2687
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Contamination of Diesel Fuel, its Interaction with Fuel Additives and the Resultant Effects on Filter Plugging and Injector Fouling

Abstract: Diesel fuel distilled from crude oil should contain no greater than trace amounts of sodium. However, fuel specifications do not include sodium; there is a limit of five parts per million for the amount of sodium plus potassium in fatty acid methyl esters (FAME) used as biodiesel. Sodium compounds are often used as the catalyst for the esterification process for producing FAME and sodium hydroxide is now commonly used in the refining process to produce ultra-low sulphur diesel (ULSD) fuel from crude oil. Good … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2014
2014
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 42 publications
3
33
0
Order By: Relevance
“…Moreover, added to the fuel as 1-litre premixes were mixtures of chemical compounds which according to the available results of tests performed at various laboratories have the greatest impact on the formation of various IDID [1,2,6,9,10,11,12,14,16]. The said pressures, where fuel heated up to 60 ºC returns many times from the injection systems overflows to the fuel tank, heating up the whole fuel system.…”
Section: Materials Used In the Testsmentioning
confidence: 99%
“…Moreover, added to the fuel as 1-litre premixes were mixtures of chemical compounds which according to the available results of tests performed at various laboratories have the greatest impact on the formation of various IDID [1,2,6,9,10,11,12,14,16]. The said pressures, where fuel heated up to 60 ºC returns many times from the injection systems overflows to the fuel tank, heating up the whole fuel system.…”
Section: Materials Used In the Testsmentioning
confidence: 99%
“…With a sodium 2-ethylhexanoate source, both the mono-acid lubricity improver and di-acid DDSA caused injector sticking and sodium carboxylate was observed on the injector needle. Testing of sodium chloride with a mono-acid lubricity improver did not result in engine running problems over the 32 hour test although EDAX studies showed very low levels of NaCl within the injector [1]. This would suggest that although NaCl does not react with the acidic species in the fuel it can still transport through the fuel system to the injector.…”
Section: Reid Et Al / Sae Int J Fuels Lubr / Volume 7 Issue 2 (Jumentioning
confidence: 95%
“…Previous testing has shown that different sodium sources will interact differently with acidic species in the fuel, such as mono-acid lubricity improvers or di-acid corrosion inhibitors. Sodium hydroxide has been shown to cause injector sticking with the di-acid DDSA [6] but in the presence of a mono-acid lubricity improver it was found to cause fuel starvation due to a blocked fuel filter [1]. With a sodium 2-ethylhexanoate source, both the mono-acid lubricity improver and di-acid DDSA caused injector sticking and sodium carboxylate was observed on the injector needle.…”
Section: Reid Et Al / Sae Int J Fuels Lubr / Volume 7 Issue 2 (Jumentioning
confidence: 99%
See 1 more Smart Citation
“…Contamination of diesel fuel with sodium, potentially originating from salt dryers, has been proposed as a factor in recent incidents of diesel filter plugging and injector fouling (Schwab et al 2010, Barker et al 2013. While this does not represent a direct route to contamination of gasoline with NaCl, there are situations where gasoline or denatured fuel ethanol can come into contact with diesel fuel, for example in transport trucks that have not been properly cleaned.…”
Section: Sodium and Calcium Chloride Use In Dryersmentioning
confidence: 99%